Type I Congenital Plasminogen Deficiency Is not a Risk Factor for Thrombosis - Shigekiyo, T; Uno, Y; Tomonari, A; Satoh, K; Hondo, H; Ueda, S; Saito, S (Thrombosis and Haemostasis, 1992)
The risk of thrombosis in type I congenital plasminogen (PLG) deficiency has been suggested, but is still not confirmed. We studied 40 members of two unrelated families with this disease, and found that 21 were heterozygotes of type I congenital PLG deficiency. Three of them had thrombosis, but the other 18 had no thrombosis. The percentages of family members with no history of thrombosis up to a given age among subjects with type I congenital PLG deficiency and healthy controls were analyzed by the Kaplan-Meier method. No significant difference between the two groups was observed by the generalized Wilcoxon test (p = 0.23). These results suggest that there is no significant correlation between type I congenital PLG deficiency and thrombosis.